Peran Drama Korea dalam Penguatan Moral Knowing pada Remaja - Yulianti, Yulianti; Lindawati, Yustika Irfani (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
The background of this research is the proliferation of the Korean wave phenomenon, one of the products of the Korean wave that is very much loved by the younger generation in Indonesia is Korean drama. A show can be a medium for transferring knowledge, including the moral knowledge represented by the show. In this study, researchers focused on aspects of moral awareness and perspective taking. These two aspects are very easily influenced by individual external factors such as the social environment, what is heard and seen will be a consideration for someone to think and act. This study used a quantitative method with the research technique used was a survey involving FKIP students as research respondents. The data collection process was carried out using a questionnaire containing 23 questions with a closed question model. The results of this study are in the form of descriptive statistics from the results of processing the questionnaire data that has been carried out by researchers. The discussion explains in more detail the role of Korean dramas in strengthening the moral knowledge of the respondents, who in this case are students, especially in the components of moral awareness and perspective taking. The researcher concluded that Korean drama has a role as a disseminator and socialization process of values, norms, interaction patterns, mindsets, habits, and ethics of South Korean society which will become new moral knowledge for the audience, namely students who are still in the youth category.